Clinical management of borderline personality disorder in behavioral therapies: Literature review (Research, Society and Development, 2024)
The literature on Borderline Personality Disorder (BPD) shows that it has great impacts on the personal and social lives of affected individuals, as well as on the lives of their family members and those close to them. This work is an narrative literature review and aims to analyze Brazilian productions on the clinical management of borderline personality disorder in behavioral therapies. The searches were carried out in some databases and were carried out over a period of ten years and four months (Jan/2012 – Apr/2022). A total of 17,076 articles were found, and after using the inclusion and exclusion criteria, a total of nine articles remained. Regarding the main characteristics of care for people with BPD, this work presents information on emotional dysregulation, gender prevalence, the therapeutic relationship, clinical management, the main theories and techniques used, diagnosis, treatment and effective strategies in therapies behavioral. In relation to Brazilian productions on BPD, the studies evaluated confirmed that there are productions, but studies with this audience are scarce, especially on the therapeutic relationship and clinical interventions.